(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Tumor markers are often very helpful to diagnose, staging, treatment planning and following up of the cancer patients. But still deluge of tumor markers often presents an unethical excess laboratory experience of the patients which is neither helpful nor necessary. So this is the appropriate time to think again about the accuracy of the tests to measure the parameters without error, the precision of the tests to measure the parameter they intend to measure. Our acceptance or rejection of a tumor marker testing must be guided by statistical validity of the test with an appropriate and knowledge based cut-off value determination. Statistical analysis of the tumor marker should be proportional to the empirical judgments of the clinicians. For the clinicians it is a duty to advise not only for all the tests needed for appropriate treatment but also advise only the tests those are direly needed. Otherwise tumor markers which should be an important weapon to fight against cancer will be another burden over the cancer patients. In this article we intended to focus on the technical and statistical side of different tumor marker test most concentrated around the breast cancer tumor markers. But still this review may be concerned relevant and universal for each and every cancer type and tumor markers. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i2.21080